Bulk superconductors: a roadmap to applications. (11th September 2018) - Durrell, John H; Ainslie, Mark D; Zhou, Difan; Vanderbemden, Philippe; Bradshaw, Tom; Speller, Susannah; Filipenko, Mykhaylo; Cardwell, David A
Abstract: Progress in superconducting bulk materials has been somewhat overshadowed by the considerable effort required to produce practical long-length conductors. There has, however, been steady progress in both the materials science of bulk superconducting materials and the technologies required to use them effectively in engineering applications. In particular, magnetised bulk superconductors are capable of acting as quasi-permanent magnets with the potential of providing magnetic fields of several tesla or greater from a small volume of material, they can act as magnetic shields and they can provide self-stabilised levitation. This roadmap, based on a workshop which involved the participation of a wide range of academic and industrial participants (see doi:10.17863/CAM.586 for details of the workshop methodology), aims to explore some of the key potential domains of application of bulk superconductors. Detailed technological roadmaps are presented for four key applications that were identified as providing both good market opportunity and feasibility. These are: portable systems for bulk superconductivity; portable, high-field magnet systems for medical devices; ultra-light superconducting rotating machines for next-generation transport & power applications; and magnetic shielding applications for electric machines, equipment and other high-field devices.